Exposure to chemicals formed from natural processes is ubiquitous. (13th May 2020) - Smith, Carr Joseph; Perfetti, Thomas A
Exposure to chemicals produced by natural processes is ubiquitous. First, in addition to the products of normal metabolism produced in humans of normal body weight, adipose tissue produces a large number of chemicals, including estrogen, testosterone from the produced estrogen, thyroid-stimulating hormone, leptin and approximately 500 other molecules termed adipokines, and a large number of inflammatory mediators. Second, the gut biome contains approximately the same number of bacteria as cells found in the entire body and produces a large number of small molecules. Third, the overwhelming majority (99.9%) of pesticide exposure occurs during ingestion of natural plant pesticides from eating vegetables. Fourth, consumption of cooked muscles meats leads to significant exposure to mutagenic and carcinogenic heterocyclic amines, polycyclic aromatic amines, and nitropyrenes. Fifth, many common beverages, for example, beer, coffee, and tea contain organic chemicals that display mutagenic activity. As compared with man-made production levels, from 1945 to 2015, an estimated 5000-fold more organic compounds were produced by a variety of natural processes, including common wood-degrading and forest litter-degrading fungi, microorganisms in temperate and boreal forest soils, bacteria in marine sponges, marine macro-algae, volcanoes, and forest fires. Exposure to these naturally produced organic compounds occurs via inhalation of ambient air, ingestion of food and water, and contact with soil, freshwater, and seawater. Contact with several thousand different endogenous or exogenous chemicals per day is unavoidable. This understanding might assist in better allocating resources toward controlling exposures to agents of highest concern as determined by current concepts of chronic disease causation.